(untitled) (Journal of the Spanish Institute for Strategic Studies, 2024)
The European Union (EU) tackles an unstable geopolitical context characterized by new global challenges and threats, which underscore the necessity of endowing the EU with strategic autonomy. In pursuit of this objective, an action plan named "Strategic Compass" has been adopted, aiming to enhance European strategic autonomy in the realm of security and defense. However, political, industrial, and operational dimensions hinder this endeavor, primarily due to the absence of a strong concept of strategic autonomy, challenges in joint strategic planning, the inability to align strategic cultures in the short to medium term, and the presence of divergent needs and asymmetric resources. Consequently, a disparity between expectations and reality emerges, potentially undermining the EU’s capacity to assert itself as a solid geopolitical actor on the international sphere.